Pengembangan Media Komik Digital Berbasis Kearifan Lokal Sumbawa “Basiru” Pada Mata Pelajaran Pendidikan Pancasila Kelas IV SDN 02 Meraran - Adelia, Mita; Nurhasanah; Gozin Najah Rusyada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a digital comic learning media based on the Basiru tradition, a local wisdom of Sumbawa, for the Gotong Royong topic in Pancasila Education for fourth-grade elementary school students. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were 20 fourth-grade students of SDN 02 Meraran. Data were collected through validation questionnaires completed by material and media experts, as well as practicality response questionnaires completed by the teacher and students. The data were analyzed using a five-point Likert scale and converted into percentages. The findings revealed that the digital comic achieved a validity score of 92% from the material expert, categorized as very valid, and 80% from the media expert, categorized as valid. The practicality test results showed scores of 91% in the small-group trial, 88.5% in the large-group trial, and 86.67% from the teacher, all categorized as very practical. The overall feasibility score reached 87.11%, indicating that the developed media was highly feasible. These findings demonstrate that the Basiru-based digital comic learning media is valid and practical, making it suitable for use as a supporting learning medium in Pancasila Education for fourth-grade elementary school students.